2017
DOI: 10.1016/j.lungcan.2016.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Personalizing NSCLC therapy by characterizing tumors using TKI-PET and immuno-PET

Abstract: Non-small cell lung cancer (NSCLC) therapy has entered a rapidly advancing era of precision medicine with an ever increasing number of drugs directed against a variety of specific tumor targets. Amongst these new agents, tyrosine kinase inhibitors (TKIs) and monoclonal antibodies (mAbs) are most frequently used. However, as only a sensitive subgroup of patients benefits from targeting drugs, predictive biomarkers are needed. Positron emission tomography (PET) may offer such a biomarker for predicting therapy e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…Indicated modalities for NSCLC, including tyrosine kinase inhibitors and monoclonal antibodies that target either EGFR, ALK or PD1, have been demonstrated to improve clinical outcome in target-positive tumors. In patients with target-negative tumors, however, most of these drugs have showed very limited impact [2]. In the present study, we have shown efficacy of AG-1031 in the treatment of NSCLC in animal models and it remains of interest to further explore if we can offer a combinational therapy with above targeted drugs, including tyrosine inhibitors and monoclonal antibodies, to maximize the efficacy for NSCLC treatment.…”
Section: Plos Onementioning
confidence: 64%
See 2 more Smart Citations
“…Indicated modalities for NSCLC, including tyrosine kinase inhibitors and monoclonal antibodies that target either EGFR, ALK or PD1, have been demonstrated to improve clinical outcome in target-positive tumors. In patients with target-negative tumors, however, most of these drugs have showed very limited impact [2]. In the present study, we have shown efficacy of AG-1031 in the treatment of NSCLC in animal models and it remains of interest to further explore if we can offer a combinational therapy with above targeted drugs, including tyrosine inhibitors and monoclonal antibodies, to maximize the efficacy for NSCLC treatment.…”
Section: Plos Onementioning
confidence: 64%
“…Most recently, two monoclonal antibody-based drugs (nivolumab and pembrolizumab) that specifically target programmed cell death 1 (PD-1) were approved by the Food and Drug Adminstration for the treatment of advanced NSCLC following the first line therapy. Nevertheless, overall response rates to both agents were low [2], indicating that PD1-positive patients belong to a small group within the NSCLC population. The absence of targetable mutations in approximately 50% of NSCLC cases underscores the importance for developing alternative therapeutics for NSCLC treatment.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The antibody was labeled with a positron-emitting radionuclide as a tracer. The PET system can enable visualization of the antibody delivery from pairs of gamma rays emitted indirectly by the labeled tracer [ 33 ]. This immuno-PET is better than fluorescent imaging for deep tissue imaging because of its high sensitivity and accurate quantification.…”
Section: Immuno-pet Imagingmentioning
confidence: 99%
“…Most lung cancers originate in the lung carcinomas (epithelial tissue of the internal organs) and divide into nonsmall-cell lung cancer (NSCLC) [7], [8] and small-cell lung cancer (SCLC) [9]. SCLC is a critical type of lung cancer, caused by smoking and also responsible for diagnosing cases [10].…”
Section: Introductionmentioning
confidence: 99%